A method for increasing the power of a half-cut solar cell module
In the passivation process of the solar cell half-slicing, the method of controlling the air source flow and laser treatment in the chemical vapor deposition chamber is used to solve the problem of winding plating in conventional deposition processes, and the module power and production efficiency are improved.
Patent Information
- Application Number
- CN202411863952.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-18
AI Technical Summary
In the passivation process of semi-slicing solar cell cells, conventional deposition processes cause the gas source to diffuse between the solar cell cells during the deposition of the alumina film layer, causing severe winding and affecting the power of the component.
The method of vacuuming in the chemical vapor deposition chamber is adopted to control the gas source flow rate, so as to form the gas pressure in the gap between adjacent solar cells to be greater than the gas pressure in the chemical vapor deposition chamber to prevent the gas source from entering the gap. At the same time, a laser light source is used to irradiate and heat up the alumina film layer, activate the film layer and improve the passivation effect.
The generation of winding plating is effectively reduced, the absorption rate of light by the semi-slicing of solar cell cells is improved, and the power of the component is further improved. Laser processing is more efficient than traditional heating methods, preventing high temperatures from affecting the inside of the battery and improving production efficiency.
Smart Images

Figure CN119325300B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic cells, and in particular to a method for improving the power of a half-slice assembly of a solar cell. Background Art
[0002] In the pursuit of cost reduction and efficiency improvement of photovoltaic cells, new technologies have emerged one after another, such as Selective Emitter (laser SE), Laser-enhanced contact optimization (LECO), laser selective thinning laser process (poly finger) on the back, etc. Many optimizations have been made for component power loss, such as improvement and lossless cutting of Ethylene vinyl acetate (EVA) film for encapsulation, etc. The half-cut surface of the cell cut by laser module has no passivation film and has large surface compounding, which affects the cell efficiency and component power.
[0003] In order to improve the cell efficiency and module power of half-sliced solar cells, researchers have focused on the passivation of the cut surface after the solar cell is cut in half to repair the module power loss caused by the laser cutting of the module. The current mainstream technology is to cut the half cell after LECO, and then deposit and passivate the cut surface with an aluminum oxide film. In order to ensure the passivation effect of the aluminum oxide film under low-temperature annealing or no annealing, the deposition thickness of the aluminum oxide film in the current process is usually thicker, and the thickness is generally above 50nm. There are the following technical problems: the thicker aluminum oxide film layer will cause more serious wrap-around plating on the half-sliced solar cell, which will not only affect the appearance of the half-sliced solar cell module, but also the wrap-around plating area will affect the absorption of light by the half-sliced solar cell, ultimately affecting the cell efficiency and module power; in addition, the existing processes mostly use low-temperature annealing or no annealing conditions, which cannot completely activate the aluminum oxide film, resulting in the passivation effect not being improved to the best.
[0004] A Chinese patent document discloses a "method and device for passivating and repairing damage caused by cutting half a solar cell", and its application publication number is CN 117926227A. The patent document deposits an aluminum oxide layer and an aluminum nitride layer on the surface of the sliced section of the sliced solar cell in sequence to passivate and repair the damage caused by laser cutting of the half-cut solar cell, so that the efficiency of the repaired half-cut solar cell is improved by 0.1~0.3%. However, the conventional deposition process is used to deposit the aluminum oxide layer in the patent document. During the deposition process, the gas source will inevitably disperse in the gap between the solar cells, causing a relatively serious plating phenomenon in the half-cut solar cell, affecting the absorption of light by the half-cut solar cell, resulting in poor efficiency improvement of the solar cell assembly. Summary of the invention
[0005] In view of the shortcomings of the prior art described above, the purpose of the present invention is to provide a method for improving the power of a half-slice module of a solar cell, so as to solve the problem that the conventional passivation process of the half-slice section of the solar cell adopts a conventional deposition process to deposit an aluminum oxide layer, which has serious wrap-around plating, affects the absorption of light by the half-slice of the solar cell, and leads to poor efficiency improvement effect of the half-slice module.
[0006] To achieve the above-mentioned object and other related objects, the present invention provides a method for increasing the power of a half-cut solar cell assembly, comprising the following steps:
[0007] Step (1): providing a chemical vapor deposition chamber, wherein a carrier is disposed in the chemical vapor deposition chamber, the carrier is provided with a deposition opening, and a laser light source is disposed above the deposition opening;
[0008] Step (2): stacking the sliced solar cells and placing them in a carrier so that the sliced cross-section of the solar cell is completely exposed from the deposition opening, evacuating the chemical vapor deposition chamber, introducing N2, introducing TMA, evacuating, introducing N2, introducing water vapor, evacuating, and repeating this cycle to deposit an aluminum oxide film layer on the surface of the sliced cross-section of the solar cell;
[0009] Step (3): using a laser light source to irradiate and heat the deposited aluminum oxide film layer, perform annealing, break the vacuum and exit the cavity, and complete the passivation repair of the solar cell half-cut damage;
[0010] In step (2), in a single cycle: the total gas flow rate of TMA is controlled to be less than the total gas flow rate of N2 introduced once, and the total gas flow rate of water vapor is controlled to be less than the total gas flow rate of N2 introduced twice, so that during the process of introducing TMA and water vapor, the gas pressure in the gap between adjacent solar cells is greater than the gas pressure in the chemical vapor deposition chamber, forming a pressure difference.
[0011] The prior art uses a conventional deposition process to deposit an aluminum oxide film layer on the cross-sectional surface of a stacked solar cell slice. Although the solar cells are tightly stacked, there are still certain gaps between adjacent solar cells. The applicant has found in preliminary research that during the deposition process, the gas source used to deposit the aluminum oxide film layer, such as TMA and water vapor, will diffuse into these gaps, resulting in wrap-around plating.
[0012] In order to solve the above technical problems, the present application optimizes the deposition process of the aluminum oxide film layer by using a vacuum pumping and superimposing the flow control of the gas source to generate a pressure difference in the gap between the chemical vapor deposition chamber and the solar cell, so that during the process of passing TMA and water vapor, the gas pressure in the gap between adjacent solar cells is greater than the gas pressure in the chemical vapor deposition chamber, forming a pressure difference, creatively optimizing the deposition process from the perspective of the gas source, avoiding the gas source from entering the gap between the solar cells during the deposition process, greatly reducing the generation of plating, improving the absorption rate of light, and further improving the power of the solar cell half-cut assembly. In addition, the present application further uses a laser light source to irradiate the deposited aluminum oxide film layer, only generating heat on the cut surface to activate the aluminum oxide film layer, thereby improving the passivation effect; the laser light source heating method can effectively prevent high temperature from entering the interior of the cell and affecting the LECO effect compared to the traditional electric heating wire heating method; on the other hand, it greatly improves the heating efficiency, can achieve rapid heating, and improve production efficiency.
[0013] The anti-winding plating deposition principle of the aluminum oxide film layer mentioned in the present application is as follows:
[0014] like Figure 2 As shown, first evacuate, introduce N2 once, introduce TMA, evacuate, introduce N2 twice, introduce water vapor, evacuate, in a single cycle: introduce N2 once to ensure that N2 fills the gaps between adjacent solar cells before TMA is introduced, control the total gas flow of TMA to be less than the total gas flow of N2 introduced once, ensure that the gas pressure in the gaps between solar cells is greater than the external gas pressure when TMA is introduced, because the pressure difference causes the gas in the gaps between solar cells to flow outward all the time, reducing the possibility of TMA entering the gaps between solar cells. Then evacuate, so that the gaps between solar cells and the chemical vapor deposition chamber reach a vacuum state without any gas; then introduce N2 twice to ensure that N2 fills the gaps between adjacent solar cells before water vapor is introduced; finally, control the total gas flow of water vapor to be less than the total gas flow of N2 introduced twice, ensure that the gas pressure in the gaps between solar cells is greater than the external gas pressure when water vapor is introduced, because the pressure difference causes the gas in the battery gap to flow outward all the time, reducing the possibility of water vapor entering the gaps between solar cells.
[0015] Preferably, in step (2), the first diluted N2 is introduced at the same time as TMA, and the total gas flow rate of TMA is the sum of the flow rate of TMA and the flow rate of the first diluted N2.
[0016] Preferably, in step (2), the second diluted N2 is introduced at the same time as the water vapor is introduced, and the total gas flow rate of the water vapor is the sum of the flow rate of the water vapor and the flow rate of the second diluted N2.
[0017] Preferably, in step (2), the flow rate of N2 introduced at one time is 5000-30000 sccm, the introduction time is 1-20 s, and the gas pressure in the gap between adjacent solar cells is controlled to be 30-100 Pa. In this process, the gas is introduced into the chemical vapor deposition chamber to diffuse into the gap between adjacent solar cells and achieve pressure balance, thereby achieving control of the gas pressure in the gap between adjacent solar cells.
[0018] Preferably, in step (2), the flow rate of TMA is controlled to be 100-10000 sccm, the flow rate of the first diluted N2 is controlled to be 1000-20000 sccm, the introduction time is 1-20 s, and the gas pressure in the chemical vapor deposition chamber is controlled to be 20-70 Pa.
[0019] Preferably, in step (2), the flow rate of the secondary N2 is 5000-30000 sccm, the introduction time is 1-20 s, and the gas pressure in the gap between adjacent solar cells is controlled to be 30-100 Pa. In this process, the gas is introduced into the chemical vapor deposition chamber to diffuse into the gap between adjacent solar cells and achieve pressure balance, thereby achieving control of the gas pressure in the gap between adjacent solar cells.
[0020] Preferably, in step (2), the flow rate of water vapor is controlled to be 100-10000 sccm, the flow rate of the second diluted N2 is controlled to be 1000-20000 sccm, the introduction time is 1-20 s, and the gas pressure in the chemical vapor deposition chamber is controlled to be 20-70 Pa.
[0021] Preferably, in step (3), the power of the laser light source is controlled to be 20-100 kW, the laser wavelength is 400-500 nm, and the irradiation heating time is 2-30 s.
[0022] Preferably, in step (2), the number of cycles is 40 to 200.
[0023] Preferably, in step (2), the deposition thickness of the aluminum oxide film layer is 5-25 nm. The present application adopts a thinner aluminum oxide film layer to further reduce the probability of plating bypass. In addition, the thickness of the aluminum oxide film layer within the above range has a good waterproof and insulating effect. The deposition thickness of the above film can ensure the comprehensive production capacity and efficiency improvement of the repaired half-cell.
[0024] More preferably, the deposition temperature of aluminum oxide is 150-250°C.
[0025] As described above, the present invention has the following beneficial effects:
[0026] (1) The deposition process of the aluminum oxide film layer is optimized by using a vacuum pump and superimposed control of the flow rate of the gas source to generate a pressure difference in the gap between the chemical vapor deposition chamber and the solar cell. When TMA and water vapor are introduced, the gas pressure in the gap between adjacent solar cells is greater than the gas pressure in the chemical vapor deposition chamber, forming a pressure difference. The deposition process is creatively optimized from the perspective of the gas source, and the gas source is prevented from entering the gap between the solar cells during the deposition process. This greatly reduces the occurrence of wrap-around plating, improves the light absorption rate, and further improves the power of the half-cut solar cell module.
[0027] (2) Using a laser light source to irradiate the deposited aluminum oxide film layer, only generating heat on the cut surface to activate the aluminum oxide film layer, thereby improving the passivation effect; compared with the traditional electric heating wire heating method, the laser light source heating method effectively prevents high temperature from entering the interior of the battery cell and affecting the LECO effect;
[0028] (3) Depositing a thinner aluminum oxide film layer on the cross-section surface of the solar cell further reduces the probability of bypass plating compared to a thicker aluminum oxide film layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Shown is an enlarged schematic diagram of the structure after the carrier and solar cell are assembled.
[0030] Figure 2 Shown is a schematic diagram of the anti-wraparound deposition principle of the aluminum oxide film layer of the present application.
[0031] Figure 3 Shown is a schematic diagram of the structure of the carrier and the repaired solar cell.
[0032] Figure 4 The figure shows the appearance of the plating of half a solar cell after passivation repair in Example 1.
[0033] Figure 5 Shown is the appearance of the plating of half a solar cell after passivation repair in comparative example 1.
[0034] Figure 6 Shown is the appearance of the plating of half a solar cell after passivation repair in comparative example 3.
[0035] Description of the accompanying drawings: carrier 1, solar cell 2, slice section 3, aluminum oxide film layer 4, gap 5. DETAILED DESCRIPTION
[0036] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0037] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0038] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0039] Example 1
[0040] The present application provides a method for increasing the power of a half-cut solar cell assembly, comprising the following steps:
[0041] Step (1): Provide a chemical vapor deposition chamber, wherein the chemical vapor deposition chamber is provided with Figure 1 The carrier 1 shown is provided with a deposition opening, and a laser light source is provided above the deposition opening;
[0042] Step (2): If Figure 1 As shown, the complete cell is sliced, the cut solar cells 2 are uniformly stacked and placed in the carrier 1, and the sliced cross section of the solar cell is completely exposed from the deposition opening, the chemical vapor deposition chamber is evacuated, leak detection is performed, the temperature is raised to 200° C., the temperature is kept constant, and then aluminum oxide deposition is performed;
[0043] Once N2 is introduced: 20000 sccm of nitrogen is introduced for 10 seconds, so that the gap 5 between the solar cells is filled with nitrogen and the pressure is maintained at 80 Pa;
[0044] Introduce TMA: introduce 5000 sccm TMA and 8000 sccm first diluted N2 for 7 s, so that the pressure of the chemical vapor deposition chamber reaches 50 Pa;
[0045] Evacuate the chamber without introducing any gas, and evacuate the chamber for 10 seconds, so that the gap 5 between the solar cell panels and the external chemical vapor deposition chamber reach a vacuum state without any gas;
[0046] Secondary N2 injection: 20000 sccm nitrogen is introduced for 10 s to fill the gap 5 between the solar cells with nitrogen and maintain a pressure of 80 Pa;
[0047] Water vapor was introduced: 3000 sccm water vapor and 10000 sccm second diluted N2 were introduced for 7 s to make the pressure of the chemical vapor deposition chamber reach 50 Pa;
[0048] Vacuuming: Without introducing any gas, evacuate the chamber for 10 seconds to make the battery gap and the external chamber reach a vacuum state without any gas;
[0049] This cycle was repeated 100 times. In a single cycle, the total gas flow rate of TMA was controlled to be less than the total gas flow rate of N2 introduced once, and the total gas flow rate of water vapor was controlled to be less than the total gas flow rate of N2 introduced twice, so that during the process of introducing TMA and water vapor, the gas pressure in the gap between adjacent solar cells was greater than the gas pressure in the chemical vapor deposition chamber, forming a pressure difference, and depositing an aluminum oxide film layer with a thickness of 13 nm on the surface of the sliced section of the solar cell;
[0050] Step (3): Use a laser light source to irradiate and heat the deposited aluminum oxide film layer, with a laser wavelength of 400nm, a time of 30s, a power of 50kW, annealing treatment, break the vacuum and exit the cavity, and complete the passivation repair of the solar cell half-cut damage.
[0051] The appearance of the half-sheet of the solar cell after passivation repair in this embodiment is as follows: Figure 4 shown.
[0052] Example 2
[0053] The present application provides a method for increasing the power of a half-cut solar cell assembly, comprising the following steps:
[0054] Step (1): Provide a chemical vapor deposition chamber, wherein the chemical vapor deposition chamber is provided with Figure 1 The carrier 1 shown is provided with a deposition opening, and a laser light source is provided above the deposition opening;
[0055] Step (2): If Figure 1As shown, the complete cell is sliced, the cut solar cells 2 are uniformly stacked and placed in the carrier 1, and the sliced cross section of the solar cell is completely exposed from the deposition opening, the chemical vapor deposition chamber is evacuated, leak detection is performed, the temperature is raised to 150° C., the temperature is kept constant, and then aluminum oxide deposition is performed;
[0056] One-time introduction of N2: 30000 sccm of nitrogen is introduced for 10 s to fill the gap 5 between the solar cells with nitrogen and maintain a pressure of 100 Pa;
[0057] Introduce TMA: introduce 5000 sccm TMA and 10000 sccm first diluted N2 for 7 s, so that the pressure of the chemical vapor deposition chamber reaches 60 Pa;
[0058] Evacuate the chamber without introducing any gas, and evacuate the chamber for 10 seconds, so that the gap 5 between the solar cell panels and the external chemical vapor deposition chamber reach a vacuum state without any gas;
[0059] Secondary introduction of N2: 30000 sccm of nitrogen is introduced for 10 s to fill the gap 5 between the solar cells with nitrogen and maintain a pressure of 100 Pa;
[0060] Water vapor was introduced: 3000 sccm water vapor and 12000 sccm second diluted N2 were introduced for 7 s to make the pressure of the chemical vapor deposition chamber reach 60 Pa;
[0061] Vacuuming: Without introducing any gas, evacuate the chamber for 10 seconds to make the battery gap and the external chamber reach a vacuum state without any gas;
[0062] This cycle was repeated 200 times. In a single cycle, the total gas flow rate of TMA was controlled to be less than the total gas flow rate of N2 introduced once, and the total gas flow rate of water vapor was controlled to be less than the total gas flow rate of N2 introduced twice, so that during the process of introducing TMA and water vapor, the gas pressure in the gap between adjacent solar cells was greater than the gas pressure in the chemical vapor deposition chamber, forming a pressure difference, and depositing an aluminum oxide film layer with a thickness of 25 nm on the surface of the sliced section of the solar cell;
[0063] Step (3): Use a laser light source to irradiate and heat the deposited aluminum oxide film layer, with a laser wavelength of 500nm, a time of 10s, a power of 20kW, annealing treatment, break the vacuum and exit the cavity, and complete the passivation repair of the solar cell half-cut damage.
[0064] Example 3
[0065] The present application provides a method for increasing the power of a half-cut solar cell assembly, comprising the following steps:
[0066] Step (1): Provide a chemical vapor deposition chamber, wherein the chemical vapor deposition chamber is provided with Figure 1 The carrier 1 shown is provided with a deposition opening, and a laser light source is provided above the deposition opening;
[0067] Step (2): If Figure 1 As shown, the complete battery is sliced, the cut solar cells 2 are uniformly stacked and placed in the carrier 1, and the sliced cross section of the solar cell is completely exposed from the deposition opening, the chemical vapor deposition chamber is evacuated, leak detection is performed, the temperature is increased to 250°C, the temperature is kept constant, and then aluminum oxide deposition is performed;
[0068] Once N2 is introduced: 25000 sccm of nitrogen is introduced for 10 seconds to fill the gap 5 between the solar cells with nitrogen and maintain a pressure of 90 Pa;
[0069] Introduce TMA: introduce 5000 sccm TMA and 12000 sccm first diluted N2 for 7 s, so that the pressure of the chemical vapor deposition chamber reaches 70 Pa;
[0070] Evacuate the chamber without introducing any gas, and evacuate the chamber for 10 seconds, so that the gap 5 between the solar cell panels and the external chemical vapor deposition chamber reach a vacuum state without any gas;
[0071] Secondary N2 injection: 20000 sccm nitrogen is introduced for 10 s to fill the gap 5 between the solar cells with nitrogen and maintain a pressure of 90 Pa;
[0072] Water vapor was introduced: 3000 sccm of water vapor and 14000 sccm of the second diluted N2 were introduced for 7 s, so that the pressure of the chemical vapor deposition chamber reached 70 Pa;
[0073] Vacuuming: Without introducing any gas, evacuate the chamber for 10 seconds to make the battery gap and the external chamber reach a vacuum state without any gas;
[0074] This cycle was repeated 40 times. In a single cycle, the total gas flow rate of TMA was controlled to be less than the total gas flow rate of N2 introduced once, and the total gas flow rate of water vapor was controlled to be less than the total gas flow rate of N2 introduced twice, so that during the process of introducing TMA and water vapor, the gas pressure in the gap between adjacent solar cells was greater than the gas pressure in the chemical vapor deposition chamber, forming a pressure difference, and depositing an aluminum oxide film layer with a thickness of 5 nm on the surface of the sliced section of the solar cell;
[0075] Step (3): Use a laser light source to irradiate and heat the deposited aluminum oxide film layer, with a laser wavelength of 400nm, a time of 30s, a power of 50kW, annealing treatment, break the vacuum and exit the cavity, and complete the passivation repair of the solar cell half-cut damage.
[0076] Comparative Example 1
[0077] The difference between Comparative Example 1 and Example 1 is that the deposition process of aluminum oxide is different, and the other processes are exactly the same.
[0078] The specific deposition process of aluminum oxide in this comparative example is:
[0079] TMA: 5000 sccm TMA and 8000 sccm nitrogen were introduced for 7 s;
[0080] N2: 13000 sccm nitrogen for 10 s;
[0081] H2O: 3000 sccm water vapor and 10000 sccm nitrogen were introduced for 7 s;
[0082] N2: 13000 sccm nitrogen for 10 s;
[0083] The above steps were repeated for 100 cycles, and an aluminum oxide film layer with a thickness of 13 nm was grown on the cross section.
[0084] The appearance of the half-sheet of solar cell after passivation repair in this comparative example is as follows: Figure 5 shown.
[0085] Comparative Example 2
[0086] The difference between Comparative Example 2 and Comparative Example 1 is that the laser processing step is not included, and the other processes are exactly the same.
[0087] Comparative Example 3
[0088] The difference between Comparative Example 3 and Comparative Example 2 is that the deposition thickness of the aluminum oxide film layer is different, specifically 65 nm, and the other processes are exactly the same.
[0089] The appearance of the half-sheet of solar cell after passivation repair in this comparative example is as follows: Figure 6 shown.
[0090] Comparative Example 4
[0091] The difference between Comparative Example 4 and Example 1 is that the deposition process of the aluminum oxide film layer is not included, and the laser light source is directly used to irradiate and heat the sliced cross section of the solar cell, and the other processes are exactly the same.
[0092] Comparative Example 5
[0093] The difference between Comparative Example 5 and Comparative Example 4 is that the heating source is different, the heating time is different, specifically, the heating wire is used for heating for 300 seconds, and the other processes are exactly the same.
[0094] Comparative Example 6
[0095] Comparative Example 6 is a solar cell slice that has not been processed in any way.
[0096] The solar cell slices processed in Examples 1 to 3 and Comparative Examples 1 to 6 were packaged and the performance of the solar cell assemblies was tested. The results are shown in Table 1:
[0097] Table 1. Performance test results of solar cell slice assemblies after treatment in Examples 1 to 3 and Comparative Examples 1 to 6
[0098] Performance Indicators Aluminum oxide film layer (nm) Laser processing FF(%) Voc(V) Isc(A) <![CDATA[P max (W)]]> Example 1 13 have 80.19 58.51 13.60 638.1 Example 2 25 have 80.18 58.51 13.60 638.0 Example 3 5 have 80.18 58.49 13.60 637.8 Comparative Example 1 13 have 80.10 58.50 13.60 637.3 Comparative Example 2 13 none 79.70 58.45 13.59 633.1 Comparative Example 3 65 none 79.96 58.47 13.59 635.4 Comparative Example 4 0 have 79.47 58.42 13.58 630.5 Comparative Example 5 0 No, using heating wire 79.27 58.34 13.56 627.1 Comparative Example 6 0 none 79.46 58.41 13.58 630.3
[0099] In Table 1, FF refers to the fill factor, Voc is the open circuit voltage of the battery cell, Isc is the short circuit current of the battery cell, P max It is the power generation of the solar cell slice assembly.
[0100] Combined with Table 1, Figure 4 and Figure 5 It can be seen that the solar cell slices after repair in Example 1 have no wrap-around plating, while the solar cell slices after repair in Comparative Example 1 have slight wrap-around plating, and the module power of Example 1 is better than that of Comparative Example 1. It can be seen that the present application controls the gas pressure in the gap between adjacent solar cells to be greater than the gas pressure in the chemical vapor deposition chamber during the introduction of TMA and water vapor, thereby forming a pressure difference variable pressure source alumina deposition process, which can prevent the occurrence of wrap-around plating during the deposition of the aluminum oxide film layer and reduce the influence of wrap-around plating on the module power.
[0101] From the data in Table 1, it can be seen that by comparing the data of Comparative Example 2 with that of Comparative Example 1, laser treatment has a significant effect on improving the power of the component; Figure 5 and Figure 6 It can be seen that the solar cell slices repaired in Example 3 are more prone to plating around than those in Example 1, indicating that reducing the deposition thickness of the aluminum oxide film layer can reduce the occurrence of plating around. By comparing the data of Example 1 and Example 4, it can be seen that only laser treatment without depositing an aluminum oxide film layer cannot effectively repair the cut surface damage. This is because the laser treatment mainly activates the passivation effect of the aluminum oxide film layer. In the absence of an aluminum oxide film layer, directly using laser to treat the half-cut section of the solar cell cannot improve the passivation effect; by comparing the data of Examples 4, 5 and 6, it can be seen that the laser can quickly heat the surface of the solar cell cut surface without affecting the module power, while Example 5 uses conventional hot wire heating to easily transfer heat to the entire battery, thereby affecting the module power.
[0102] Combined with all embodiments, comparative examples and data. In the process of depositing aluminum oxide film layer, the gas pressure in the gap between adjacent solar cells is greater than the gas pressure in the chemical vapor deposition chamber by controlling the introduction of TMA and water vapor, forming a pressure difference, thereby controlling the flow direction of the gas in the gap between the cells, which can prevent the occurrence of plating around, reduce the appearance of the yield problem of the component, and prevent the cell from absorbing light without plating around, thereby improving the power of the component; laser treatment can achieve a better passivation effect under the condition of thinner aluminum oxide, and thin aluminum oxide can reduce the occurrence of plating around, reduce the risk of plating around the appearance, and laser treatment can be used to raise the required temperature on the surface of the cut surface in a shorter time, prevent the substrate from rising to a higher temperature, and reduce the impact on the LECO effect of the battery. The aluminum oxide film layer prepared by the technical solution of the present application is much thinner than the aluminum oxide film layer prepared by the existing conventional process, which greatly saves the process time, improves the production capacity, and reduces the consumption of chemicals, which is highly competitive and conducive to large-scale continuous mass production of the production line. Therefore, the present invention effectively overcomes the various shortcomings in the prior art and has a high industrial utilization value.
[0103] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for increasing the power of a half-cut solar cell assembly, characterized in that: The following steps are involved: Step (1): providing a chemical vapor deposition chamber, wherein a carrier is disposed in the chemical vapor deposition chamber, the carrier is provided with a deposition opening, and a laser light source is disposed above the deposition opening; Step (2): stacking the sliced solar cells and placing them in a carrier so that the sliced cross-section of the solar cell is completely exposed from the deposition opening, evacuating the chemical vapor deposition chamber, introducing N2, introducing TMA, evacuating, introducing N2, introducing water vapor, evacuating, and repeating this cycle to deposit an aluminum oxide film layer on the surface of the sliced cross-section of the solar cell; Step (3): using a laser light source to irradiate and heat the deposited aluminum oxide film layer, perform annealing, break the vacuum and exit the cavity, and complete the passivation repair of the solar cell half-cut damage; In step (2), in a single cycle: the total gas flow rate of TMA is controlled to be less than the total gas flow rate of N2 introduced once, and the total gas flow rate of water vapor is controlled to be less than the total gas flow rate of N2 introduced twice, so that during the process of introducing TMA and water vapor, the gas pressure in the gap between adjacent solar cells is greater than the gas pressure in the chemical vapor deposition chamber, forming a pressure difference.
2. The method for increasing the power of a half-cut solar cell assembly according to claim 1, characterized in that: In step (2), the first diluted N2 is introduced at the same time as TMA, and the total gas flow rate of TMA is the sum of the flow rate of TMA and the flow rate of the first diluted N2.
3. The method for increasing the power of a half-slice solar cell assembly according to claim 1, characterized in that: In step (2), the second diluted N2 is introduced at the same time as the water vapor is introduced, and the total gas flow rate of the water vapor is the sum of the flow rate of the water vapor and the flow rate of the second diluted N2.
4. The method for increasing the power of a half-cut solar cell assembly according to claim 1, characterized in that: In step (2), the flow rate of N2 is 5000-30000 sccm, the introduction time is 1-20 s, and the gas pressure in the gap between adjacent solar cells is controlled to be 30-100 Pa.
5. According to the method for increasing the power of a half-slice solar cell assembly as described in claim 2, in step (2), the flow rate of TMA is controlled to be 100-10000 sccm, the flow rate of the first diluted N2 is controlled to be 1000-20000 sccm, the introduction time is 1-20 s, and the gas pressure in the chemical vapor deposition chamber is controlled to be 20-70 Pa.
6. The method for increasing the power of a half-cut solar cell assembly according to claim 1, characterized in that: In step (2), the flow rate of the secondary N2 is 5000-30000 sccm, the introduction time is 1-20 s, and the gas pressure in the gap between adjacent solar cells is controlled to be 30-100 Pa.
7. The method for increasing the power of a half-cut solar cell assembly according to claim 3, characterized in that: In step (2), the flow rate of water vapor is controlled to be 100-10000 sccm, the flow rate of the second diluted N2 is controlled to be 1000-20000 sccm, the introduction time is 1-20 s, and the gas pressure in the chemical vapor deposition chamber is controlled to be 20-70 Pa.
8. The method for increasing the power of a half-slice solar cell assembly according to claim 1, characterized in that: In step (3), the power of the laser light source is controlled to be 20-100 kW, the laser wavelength is controlled to be 400-500 nm, and the irradiation heating time is controlled to be 2-30 s.
9. The method for increasing the power of a half-cut solar cell assembly according to claim 1, characterized in that: In step (2), the number of cycles is 40 to 200 times.
10. The method for increasing the power of a half-cut solar cell assembly according to claim 1, characterized in that: In step (2), the deposition thickness of the aluminum oxide film layer is 5 to 25 nm.
Citation Information
Patent Citations
Solar battery piece half-piece cutting damage passivation repairing method and solar battery piece half-piece cutting damage passivation repairing device
CN117926227A
Crystalline silicon solar cell and edge passivation method thereof
CN111430506A
Process for passivating photovoltaic cells and process for producing passivated photovoltaic sub-cells
CN113330585A